Implementasi Website E-ABK Terkait Kinerja Pegawai di Badan Pembangunan Perencanaan Daerah, Penelitian dan Pengembangan Kota Surabaya - Syahrani, Regita Pinkan (VISA: Journal of Vision and Ideas, 2024)
Workload Analysis is a management technique that is carried out systematically to obtain information about the level of effectiveness and efficiency of an organization's work based on work volume. The results of this analysis can be the basis for increasing work productivity and taking other steps in the development, improvement, and utilization of human resources in the government. One of the important innovations in this field is the application of electronic Workload Analysis (E-ABK). With E-ABK, the workload assessment process becomes more objective and transparent. The data collected covers various aspects of the job, from routine tasks to non-routine activities, providing a comprehensive picture of each employee's contribution. The purpose of this study is to explain to readers the process of working and filling workloads through the E-ABK website related to employee performance results, The benefits of implementing workload analysis in an agency for employees and the agency. In this journal using qualitative research methods, the process of collecting data and information related to this research was obtained by conducting interviews, observations, and documentation studies. The author uses 4 research focuses, namely, Communication, Resources, Bureaucratic Structure, and Disposition. The results of this study show that the implementation of the E-ABK website at the Regional Development Planning Agency, Research and Development of the City of Surabaya has been running optimally in accordance with the implementation theory according to Edward III.